Prevalence and genetic diversity of porcine circovirus type 2 in northern Guangdong Province during 2016–2021 - Nan, Wenjin; Wu, Jingbo; Hu, Honghui; Peng, Guoliang; Tan, Simin; Deng, Zhibang (Frontiers in Veterinary Science, 2022)
The emergence and widespread of porcine circovirus-associated diseases (PCVADs), mainly caused by porcine circovirus type 2 (PCV2), threatens the the Chinese swine industry. In this study, to investigate the recent prevalence of PCV2 in northern Guangdong Province of China, 573 tissue samples from 132 pig farms were collected during 2016-2021 and analyzed via PCR. Overall, 51.38% (297/573, 95%CI 47.74-55.92) samples were tested PCV2 positive. The detection rate of PCV2 was significantly lower in samples collected before 2016-2018 than after the outbreak of African Swine Fever (2019-2021), being 59.85% (158/264, 95%CI 53.94-65.76) and 41.47% (141/340, 95%CI 36.43-46.71), respectively. On the other end, the genetic characteristics of 26 PCV2 strains were further analyzed. These PCV2 strains belonged to three genotypes, including PCV2a, PCV2b, and PCV2d. Specifically, the predominant genotype prevalent during two periods (2016~2018 and 2019~2021) wasPCV2b (81.82%, 9/11) and PCV2d (80.0%, 12/15), respectively. The results above illustrated the high prevalence and the genetic evolution feature of PCV2 in Guangdong Province in recent years.